PENERAPAN SISTEM AMONG DALAM PROSES PENDIDIKAN SUATU UPAYA MENGEMBANGKAN KOMPETENSI GURU - Siti Masitoh; Fibria Cahyani (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
Professional teachers were required having four competencies as mandated by Teachers Law No. 14 of 2005. Those competencies were: (1) pedagogic, (2) professional, (3) personal, and (4) social competence. They seemed to Ki Hajar Dewantara's thoughts were explicitly reflected in Tamansiswa principles, namely: (1) orderly speaking and acting, (2) greetings, (3) peace, and (4) happiness. They accord to regulation of national education minister No. 16 of 2007, including "Presenting yourself as an honest person, noble character, and revealing good model for students and society." The toughts of Ki Hajar's personality was translated into values that must be possessed by educators and educated. These values were, (1) exemplary: ing ngarsa sung tulada; (2) motivation: ing madya mangun karsa; (3) tut wuri handayani is in the implementation of education is called the nurture system. Data collection techniques was using method: questionnaire, observation, interview, and documents. Data analysis techniques also used flow analysis adaptation of Milles and Huberman (2013). The research findings were: (1) lecturers' behavior in conducting education with the nurture system at UST Yogyakarta in building character has been internalized in lecturers, employees, and students reflected in campus life. Referring to Tamansiswa principles, Ki Hajar Dewantara's thoughts were consisting to: (a) Niteni, Nirokake, Nambahi, (b) Tri Nga: Ngerti, Ngroso, Nglakoni, and (c) the implementation of leadership trilogy in the nurture system stood for wider seven Tamansiswa principles. Ki Hajar's thoughts were expected to be implemented by the teachers as educator by giving good model in carrying out education.AbstrakGuru profesional dituntut memiliki empat kompetensi seperti yang diamanahkan oleh Undang-Undang Guru No 14 Tahun 2005. Kompetensi yang dimaksud, yaitu kompetensi: (1) pedagogik, (2) profesional, (3) kepribadian, dan (4) kompetensi sosial. Dalam penerapan keempat kompetensi guru tersebut secara terintegrasi. Ajaran Ki Hajar Dewantara yang tersurat dalam azas tamansiswa, yaitu (1) tertib bicara dan bertindak, (2) salam, (3) damai, dan (4) bahagia. Keempat azas tamansiswa ini selaras dengan Permendiknas No. 16 Tahun 2007, di antaranya “Menampilkan diri sebagai pribadi yang jujur, berakhlak mulia, dan teladan bagi peserta didik dan masyarakat.” Ajaran kepribadian Ki Hajar dapat dijabarkan menjadi nilai-nilai yang harus dimiliki oleh pendidik, dan terdidik. Nilai-nilai tersebut yaitu, (1) keteladanan: ing ngarsa sung tulada; (2) motivasi: ing madya mangun karsa; (3) tut wuri handayani dalam plaksanaan pendidikan disebut sistem among. Teknik pengumpulan data menggunakan metode: angket, observasi, wawancara dan dokumen. Teknik analisis data menggunakan analisis alir adaptasi Milles dan Huberman (2013). Hasil penelitian ditemukan: (1) perilaku dosen dalam melaksanakan pendidikan dengan sistem among di UST Yogyakarta dalam membangun  karakter sudah terinternalisasi pada dosen, tendik dan mahasiswa yang tercermin dalam kehidupan kampus. dengan berlandaskan azas tamansiswa. Ajaran Ki Hajar Dewantara di antaranya: (a) Niteni, Nirokake, Nambahi, (b) Tri Nga: Ngerti, Ngroso, Nglakoni, dan (c) penerapan trilogi kepemimpinan dalam sistem among dengan berpijak pada tujuh azas tamansiswa yang diperluas. Ajaran Ki Hajar ini diharapkan dapat diterapkan oleh guru sebagai pendidik dengan keteladanan dirinya dalam melaksanakan pendidikan